2019
DOI: 10.1042/bsr20190052
|View full text |Cite
|
Sign up to set email alerts
|

Yi-qi-yang-yin-tian-sui-fang enhances cisplatin-induced tumor eradication and inhibits interleukin-7 reduction in non-small cell lung cancer

Abstract: Traditional Chinese Medicine (TCM) has been recognized to be conducive to enhancing the efficiency and reducing the side effects in the whole course of cancer treatment. The mechanisms of TCM/chemotherapy combination involved with interleukin-7 (IL-7) potentially enhance immune responses against tumor. In the present study, we emphasized on a herbal formulation Yi-qi-yang-yin-tian-sui-fang or TCM for short, and investigated its roles in chemotherapy in non-small cell lung cancer (NSCLC). The mice bared with tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The preparation of blank serum was the same as that of drug-containing serum preparation, but rats were administered the same amount of normal saline. The serum of the same group was merged, inactivated at 56°C for 30 min, filtered by using a 0.22 μ m microporous membrane, and stored at −20°C for later use [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of blank serum was the same as that of drug-containing serum preparation, but rats were administered the same amount of normal saline. The serum of the same group was merged, inactivated at 56°C for 30 min, filtered by using a 0.22 μ m microporous membrane, and stored at −20°C for later use [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, YYD was found to enhance the apatinib sensitivity in mid-advanced NSCLC [ 17 ]. YYD also promoted cisplatin-induced tumor eradication and suppressed interleukin-7 reduction in NSCLC [ 18 ]. However, the biological functions and pharmacological mechanisms of YYD in inhibiting NSCLC have not been comprehensively investigated with appropriate methods.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, with the continuous elucidation of the anti-tumor mechanism of traditional Chinese medicine (TCM), various clinical data demonstrated that TCM had the advantages of multiple targets, multiple pathways, and multiple layers 8 . TCM has been recognized to be conducive to enhancing e ciency and safety, especially having signi cant impacts on killing cancer cells, decreasing side effects of chemoradiotherapy, and thereby prolonging the overall survival time of patients 9,10 At present, there is a lack of evaluation on the e cacy and safety of TCM combined with apatinib in the treatment of AGC. Therefore, the study aimed to evaluate the effectiveness and safety of XYG combined with aptinib in the treatment of AGC who failed radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%